1972
DOI: 10.1037/h0032545
|View full text |Cite
|
Sign up to set email alerts
|

Social rehabilitation of isolate-reared monkeys.

Abstract: Numerous researches have indicated that 6 or more months of total social isolation initiated at birth produces profound and apparently permanent social deficits in rhesus monkey subjects. Monkeys so reared fail to develop appropriate play, aggressive, sexual, and maternal behaviors but instead exhibit self-directed abnormalities such as self-clasping, huddling, and stereotypic rocking behaviors. Previous experimentation designed to rehabilitate isolate-reared subjects has not been successful. The present exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

1974
1974
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(93 citation statements)
references
References 10 publications
4
88
0
1
Order By: Relevance
“…Both human and animal work clearly shows that this is not true (Clark & Hanisee, 1982;Skeels, 1966;Suomi & Harlow, 1972). Babies suffering from malnutrition and reared in stultifying institutions or war-torn lands do show signs of their abuse and neglect.…”
Section: The Slow Rate Of Growing Up: Consequence To Human Evolutionmentioning
confidence: 99%
“…Both human and animal work clearly shows that this is not true (Clark & Hanisee, 1982;Skeels, 1966;Suomi & Harlow, 1972). Babies suffering from malnutrition and reared in stultifying institutions or war-torn lands do show signs of their abuse and neglect.…”
Section: The Slow Rate Of Growing Up: Consequence To Human Evolutionmentioning
confidence: 99%
“…A massive body of research has shown that social behavioral repertoires of isolate-reared monkeys are grossly deficient and that isolate-reared monkeys respond less to social stimuli than do monkeys reared from birth with conspecifics [H a r lo w and H a r l o w , 1965; R o w l a n d , 1964; Sackett, 1965]. Suomi et al [1972], among others, have interpreted isolates' social incompetence partially in terms of a learning deficit derived from a lack of interactive exposure with social stimuli. In this light, the present findings seem more plausible, because the subjects' sessions represented only their first 1 'A h of physical exposure to conspecifics, and this time may have been insufficient to develop differential responses to a peer as opposed to a furry stuffed object somewhat similar in size and appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Suomi and Harlow [1972] hypothesized that aggressive behavior matures not before 3 or 4 months of age in rhesus monkeys, later than affiliative behavior.…”
Section: Development O F Social Skills (Competencies)mentioning
confidence: 99%
“…In the present investigation, the subjects were: (1) visually and physically isolated from conspecific experience, as opposed to, e.g., Anderson and Mason [1974], Kaplan [ 1977], and Roy et al [ 1978], but at the same time (2) provided not only with a mother sur rogate but also with daily additional substi tute stimulation in order to counteract devel opmental pathology; (3) as young as feasible but sufficiently developed in their basic mo tor and expressive behavioral repertoire [Harlow et al, 1971]; (4) met peers of equal pre-experience instead of a teacher or thera pist [Suomi and Harlow, 1972],…”
Section: Subject Age In Weeksmentioning
confidence: 99%